Старіння населення як проциклічний фактор і причина зростання фінансового сектора - Попадинець, Олена Василівна; Яцина, Вікторія Валентинівна (НТУ "ХПІ", 2016)
Актуальність дослідження зумовлена відсутністю глибокого аналізу взаємозвязку демографічних процесів та процесу надшвидкого зростання фінансового сектору. В статті розглядаються погрозливі прояви надшвидкої фінансизації, яка стала дієвим проциклічним чинником. Ці процеси багато в чому спровоковані зростанням норми збереження через всеохоплююче старіння населення і бажання людей в умовах реформування пенсійної та медичної системи забезпечити добробут в період старості. Накопичення капіталу викликають зміни у функціонуванні і параметрах рівноваги відповідного ринку.

The relevance of this study is due to comprehensive analysis lack of demographic processes interrelation and ultrafast growth process at the financial sector. The authors consider the threatening consequences of ultrafast financialization, including: a sharp increasing the financial sector share at the world's GDP, the dominance of the financial markets volumes compared with the actual ones, many companies have income from financial operations more than income from industrial activity, the population actively uses various financial tools to ensure their welfare. As a result the financialization has become a powerful reason for the cyclical economy development. These processes have been provoked by savings rate growth in the conditions of a population ageing and people's desire to ensure its own comfort and welfare in old age. The ratio growth of retirees to the working population has started throughout the world. It has become a real threat to the economies of Europe and Japan. Within a few decades it will become a problem in the United States, China, India and other countries. Population aging means the costs increasing for the pension and health care. It leads to necessity of pension and health care systems reforming in a limited state budget conditions. Large-scale transition from redistribution to the funded pension system, when incomes and living standard of each individual depends on his savings at a younger age has started at many countries. State will be forced to ensure a smaller volume of free medical services in the near future. So, people need to save money for treatment at the aging period on their own. Capital accumulation causes a change in the functioning and equilibrium parameters of the relevant market.
Population ageing as a pro-cyclical factor and the reason of the financial sector growth
Keywords: сектор фінансовий; заощадження; пенсійна система; старіння населення; бебібум; процентна ставка; financial sector; savings; pension system; population ageing; babyboom; interest rate